Présences de la diaspora arménienne en Grèce après le traité de Lausanne - Nicolas Pitsos (Cahiers Balkaniques)
Abstract: this paper proposes an overview of the formation of a Greek-Armenian community in Greece after 1923. On the one hand, the context of Armenian refugees’ settlement, their distribution within the Greek territory as well as the demographic dynamics of this population throughout the 20th century are studied. On the other hand, the social organisation and the cultural life of this community are also portrayed.